Constipation Increases Disability and Decreases Dopamine Levels in the Nigrostriatal System through Gastric Inflammatory Factors in Parkinson’s Disease - Zhou, Yongtao; Su, Yusheng; Xu, Weihua; Wang, Wei; Yao, Shukun (Current Neurovascular Research, 2019)
Objective: Recent studies suggest that not only is constipation a clinical marker of premotor phase in Parkinson’s Disease (PD), but is also correlated with the duration and severity. Some reports indicated that inflammatory from gut dysbiosis might be involved in the pathogenesis of PD, but the correlation between them remains poorly understood. This study aims to investigate how the presence of constipation affects the dopamine level of nigrostriatal system and whether gastrointestinal (GI) inflammation is involved in the brain-gut axis. Methods: Clinical materials, serum inflammatory factors, and datum of dopamine level including 84 cases and 83 controls, were collected consecutively and randomly from November 1, 2017 to October 31, 2018. Dopamine levels of nigrostriatal system were detected by [18F]-DTBZ radiotracer (18F-AV-133). Data analysis was conducted by variance, covariance analysis, bicorrelation, partial correlation, chi-square analysis and logistic regression. Results: The mean age of cases was older than that of controls, and male predominance was also observed (P<0.05). The mean scores of Hoehn-Yahr and unified Parkinson’s disease rating scale III (UPDRS-III) were of significantly different duration between two groups (P<0.05). The total dose of levodopa was not different between two groups (P>0.05). The dopamine levels of putamen and caudate nucleus, especially in the dorsal part of putamen, were significantly decreased in cases than that in controls (P<0.05). There were significant differences of complement 3 (C3) and complement 4 (C4) between cases and controls (P<0.05). Dopamine levels in putamen and caudate nucleus were negatively correlated with serum concentrations of immunoglobulin A (IgA), immunoglobulin G (IgG) and C3 in cases (P<0.05). But we did not observe similar negative correlations in controls (P>0.05). Conclusion: The presence of constipation may increase the severity of motor symptoms and decrease dopamine levels of nigrostriatal system in PD. Inflammatory factors may be involved in the brain-gut axis of PD.
Keywords: inflammation